Guiding practice principles for clinicians who work with Indigenous people - André Schultz; André Schultz; André Schultz; Anne B. Chang; Anne B. Chang; Anne B. Chang; Donna M. Mason; Julie M. Marchant; Lesley A. Versteegh; Maree Toombs; The CRE Extended Group; JM Atack; et al. (Frontiers in Pediatrics)
Culturally safe healthcare approaches are important to improve outcomes of Indigenous people. Non-Indigenous clinicians are often ill-prepared to provide such healthcare. The NHMRC Centre for Research Excellence (CRE) especially for First Nations Children has been studying for several years how to improve clinical care for Indigenous children with respiratory disease in hospital, clinic, urban, rural and remote settings. At a CRE meeting in 2023 key themes were identified based on what we have learned. Themes were informed by research conducted by the CRE and supplemented by relevant manuscripts known to CRE members. This manuscript provides practical information to aid clinicians in providing culturally safe healthcare to Indigenous people. In brief, the provision of health information that is relevant and understandable to Indigenous patients and their families is critical for ensuring condition-specific health literacy and to allow Indigenous patients to gain autonomy over medical care provided to them and their children. Methods to facilitate effective communication between healthcare providers and patients, and the creation of a culturally safe healthcare environments are discussed. The manuscript will be of practical use to clinicians and translatable to other areas of health care.